A Study Of Kuala Lumpur Composite Index Futures (FKLI) : Technical Indicator And Value-At Risk (VaR) - Lim, Ming Chun (2008)
The first part of the study examines the predictability of technical tradimg rules on the daily return of Kuala Lumpur Composite Index Futures (FKLI) from December 1995 to June 2008. The second part of the study examines the Value-at-Risk (VaR) on FKLI.